Analisis Kebutuhan Pengembangan Media Berbasis Montessory pada Siswa Sekolah Dasar - Yussi Martha Sukma Astuti (Universitas Sains dan Teknologi Komputer, 2022)
This study aims to analyze and identify Elementary School Student’s need of using media in learning. The method in this study is a descriptive method with a qualitative approach and a quantitative approach. The samples of this study are teachers and students from three schools, there are: SDN Jatisari, SDN Wonolopo 1 and SDN Wonolopo 3. The results of this study are: (1) The media used in learning are audio, visual and audio visual media. (2) Using medias have not yet effect on improving student’s learning outcomes. (3) Teachers have not used multimedia in one lesson. (4) Students rarely conduct experiments. Montessory- based in media are needed to maximize the learning process and sharpen students’ 4C skills.